First record of Plakortis Schulze (Porifera: Homosclerophorida) from the Northeast Pacific coast, with the description of Plakortis albicans sp. nov. - Cruz-Barraza, José A.; Carballo, José L. (Zootaxa, 2005)
A new species of Plakortis Schulze, 1880 from the Pacific coast of Mexico is described, which constitutes the first record of the Plakortis genus in the Northeast Pacific coast, and the first record of Homosclerophorida in the Mexican Pacific coast. Plakortis albicans sp. nov. is characterized by its white or ivory color, by a surface sculpted by subectosomic drainage canals, and by the morphological details of its skeleton, such as the presence of diods and triods in one single class, and a tangential alveolar ectosomal skeleton formed mostly by smaller diods. The only species known in the genus Plakortis from the East Pacific Ocean is Plakortis galapagensis Desqueyroux-Faúndez & van Soest, 1997, which differs from Plakortis albicans sp. nov. mainly by having diods in two distinct size classes. So far, P. albicans is only known in one locality (Mazatlán Bay), where it is relatively abundant in cryptic habitats such as under rock.